2018
DOI: 10.3892/ol.2018.7886
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/catenin β1/microRNA 183 predicts recurrence and prognosis of patients with colorectal cancer

Abstract: Abstract. The present study assessed the association between the Wnt/catenin β1 (CTNNB1)/microRNA (miR)183 signaling pathway and the recurrence and prognosis of colorectal cancer. The expression of Wnt, CTNNB1 and miR183 in primary colorectal cancer tissue was increased compared with that in the paracarcinoma tissue. Disease-free survival and overall survival were decreased in patients with colorectal cancer and increased miR183 expression compared with those in patients with colorectal cancer and decreased mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Among the deregulated genes involved in the EMT signaling, CTNNB1, as well as JAK1 play key roles in colon cancer progression: CTNNB1 through the activation of Wnt/β-catenin signaling, and JAK/STAT pathway by regulating cell survival and proliferation, differentiation and migration 72 . Our findings are in line with previous studies showing that CTNNB1 and JAK family members are colon cancer recurrence-specific genes and prognostic biomarkers 62,[72][73][74] . Notably, we also identified NLRC4 gene, a member of NOD-like receptors in the "Inflammasome Pathway", as a novel gene related to colon cancer recurrence.…”
Section: Characterization Of Genes and Pathways Involved In Patients'supporting
confidence: 93%
“…Among the deregulated genes involved in the EMT signaling, CTNNB1, as well as JAK1 play key roles in colon cancer progression: CTNNB1 through the activation of Wnt/β-catenin signaling, and JAK/STAT pathway by regulating cell survival and proliferation, differentiation and migration 72 . Our findings are in line with previous studies showing that CTNNB1 and JAK family members are colon cancer recurrence-specific genes and prognostic biomarkers 62,[72][73][74] . Notably, we also identified NLRC4 gene, a member of NOD-like receptors in the "Inflammasome Pathway", as a novel gene related to colon cancer recurrence.…”
Section: Characterization Of Genes and Pathways Involved In Patients'supporting
confidence: 93%
“…EMT process is driven by various pathways, containing TGF-b1/Smad, Wnt/b-catenin, Notch, Hedgehog and other pathways [32]. Considering Wnt/b-catenin signalling was suggested as a downstream signalling of miR-183 [33,34,35], we further studied whether circ_0026344 could impact this signalling. Data presented in this study demonstrated that circ_0026344 was capable of repressing Wnt/b-catenin signalling via a miR-183-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-181a 3133 , miR-16 3436 and miR-133b 3739 were individually investigated in three studies. MiR-126 8, 40 , miR-133a 41, 42 , miR-182 43, 44 , miR-183 45, 46 , miR-199b 47, 48 , miR-22 49, 50 , miR-224 51, 52 , miR-24-3p 53, 54 , miR-7 55, 56 , were separately analyzed in two studies. Seven researches studied two miRs concomitantly 30, 34, 38, 39, 5759 , while the others analyzed a single miR.…”
Section: Resultsmentioning
confidence: 99%
“…Among the evaluated studies, 49 demonstrated the downregulation of miR-199b 47, 48 , miR-6852 106 , miR-302c 67 , miR-466 68 , miR-650 123 , miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-296 73 , miR-187 124 , let-7a-5p 98 , miR-132 99 , miR-206 100 , miR-148a 125 , miR-33b 76 , miR-99b-5p 120 , miR-154 78 , miR-217 126 , miR-149 79 , miR-194 80 , miR-7 56 , miR-24-3p 54 , miR-29b 127 , miR-15a 34 , miR-16 34, 36 , miR-204-5p 128 , miR-96-5p 121 , miR-193a-5p 108 , miR-100 81 , miR-133a 41 , miR-139-5p 129 , miR-124-5p 130 , miR-335 82 , miR-378 101 , miR-126 40 , miR-378a-3p 58 , miR-378a-5p 58 , miR-218 83 , miR-138 110 , miR-625 111 , miR-212 112 , miR-124 131 , miR-22 49 , miR-133b 39 , miR-193a-3p 104 , miR-195 113 and miR-30c 103 associated with worse prognosis (lower overall survival) of CRC patients. Fifty-six studies identified the upregulation of miR-181a 3133 , miR-182 43, 44 , miR-1296 84 , miR-888 64 , miR-28-5p 132 , miR-183 45, 46 , miR-200c 114 , miR-34a 133 , miR-15a-5p 134 , miR-181c 135 , miR-24-3p 53 , miR-16 35 , miR-7 55 , miR-96 86 , miR-1260b 115 , miR-20a-5p 63 , miR-517a 87 , miR-503 136 , miR-106b 88 , miR-211 137 , miR-320e 89 , miR-592 90 , miR-196a 57 , miR-196b 57 , miR-376a …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation